Spinal Cord Stimulation Modalities and Charging Systems for Optimizing Chronic Pain Management - Lin, Zhihui (Transactions on Computer Science and Intelligent Systems Research, 2024)
Chronic pain, notably in conditions like failed back surgery syndrome (FBSS), challenges healthcare systems, prompting a search for effective therapies. However, pharma treatment triggers human body’s resistance which disfunction in long-term treatment. Therefore, spinal cord stimulation (SCS) offers a promising avenue. According to the gate control theory of pain control, it is possible to control the pain signal by sending new electrical waves through spinal cord to the brain. In this paper, three SCS modalities (TCS, BURST, HF) will be introduced and evaluated according to previous studies, which mainly focus on user-friendly and nerve pain control. Besides the efficacy of SCS modalities (TCS, BURST, HF), wearable charging systems warrant scrutiny. Different charging strategies (magnetic induction, magnetic resonance coupling, radio reception) will be introduced and analyzed in detail. This paper offers a concise overview of these modalities and charging strategies, aiming to inform clinical decision-making and enhance patient outcomes in chronic pain management.